The Archives Management System is Improved in the Administration Section of the DPRD Secretariat of South Sulawesi Province - Darwis, Muh; Rizal N, Muh; Jamaluddin, Jamaluddin; Awaluddin, Awaluddin (Universitas Negeri Makassar, 2023)
All important documents, whether written or in the form of images, must be able to be found again. Therefore, the aim of this research is to find out the description of the Dynamic Records Management System in the Administration section of the DPRD Secretariat of South Sulawesi Province. This research is a qualitative descriptive study. The data collection techniques used are the observation method, interview method, and documentation method. The data analysis technique used in this research is the Miles and Huberman model of data analysis, namely data collection techniques, data reduction, data presentation, and conclusions. The number of informants in this study was 5 people, namely 1 head of the administrative sub-division and 4 administrative staff employees. The results of this research show that the archive management system is diminishing in the administrative section of the secretariat of the DPRD of South Sulawesi Province which includes the creation and receipt of dimanis archives in the form of making and recording them in agenda books, the use of domains archives includes archive lending services in the form of recording in agenda books, maintenance of dimanis archives includes storage and depreciation of archives, which includes the transfer and destruction of archives. This research can be used as reference material and knowledge about dynamic records management systems in more depth because different from previous research which used qualitative methods that focused on numbers and static, this research uses qualitative methods that focus on the process and meaning of the results. This research method focuses more on human elements, objects, and institutions, as well as the interaction relationships between these elements in an effort to understand an event, behavior, and phenomenon